Shrimp (Pandalopsis dispar) waste hydrolysate as a source of novel β–secretase inhibitors. Issue 1 (December 2016) - Li-Chan, Eunice; Cheung, Imelda; Byun, Hee-Guk
Abstract In this study, purified peptides from shrimp waste hydrolysates (SWHs) were examined for their inhibitory effects against β–secretase. During consecutive purification using a Sephadex G–25 column chromatography and high performance liquid chromatography on a C18 column, a potent β–secretase inhibitory peptide Asp–Val–Leu–Phe–His (629 Da) was isolated and identified from SWH24 by Q–TOF MS/MS and the IC50 value was determined to be 92.70 μM. The β–secretase inhibition patterns of the purified peptides were found to be competitive. Among synthesized β–secretase inhibitory peptides, Leu–Phe–His had higher β–secretase inhibitory activity than the others. The result of this study suggests that the β–secretase inhibitory peptide derived from SWH24 could be potential candidates to develop nutraceuticals and pharmaceuticals.